Magnetoresistive study of the antiferromagnetic-weak ferromagnetic transition in single-crystal La₂CuO₄+δ - Belevtsev, B.I.; Dalakova, N.V.; Savitsky, V.N.; Bondarenko, A.V.; Panfilov, A.S.; Braude, I.S. (Физика низких температур, 2004)
Resistive measurements were made to study the magnetic field-induced antiferromagnetic (AF)—weak ferromagnetic (WF) transition in the La₂CuO₄ single crystal. The magnetic field (dc or pulsed) was applied normally to the CuO₂ layers. The transition manifested itself in a drastic decrease of the resistance in critical fields of 5–7 T. The study is the first to display the effect of the AF–WF transition on the conductivity of the La₂CuO₄ single crystal in the direction parallel to the CuO₂ layers. The results provide support for the three-dimensional nature of the hopping conduction of this layered oxide.